A sensitive electrochemical sensor for bisphenol A on the basis of the AuPd incorporated carboxylic multi-walled carbon nanotubes. (15th September 2019) - Mo, Fengye; Xie, Jingwen; Wu, Tengteng; Liu, Meiling; Zhang, Youyu; Yao, Shouzhuo
Highlights: A synergetic signal amplification electrochemical sensor for BPA was developed. MWCNT was used as a support material to improve the electron transport. MWCNT-PDDA-AuPd showed enhanced electrocatalytic performance. The synergetic of the catalysis and accumulation of the MWCNT-PDDA-AuPd endow the good performance of the sensor. The lower AuPd loading and the good performance of the sensor shows great prospect in sensing. Abstract: A sensitive electrochemical sensor for BPA based on the AuPd incorporated carboxylic multi-walled carbon nanotubes (MWCNT) with synergetic amplified current signal was developed, where MWCNT was used as supporter to improve electron transport and poly (diallyldimethylammonium chloride) (PDDA) was used as dispersant for MWCNT and overcome the intrinsic van der Waals interactions between MWCNT and further increase metal NPs loading. The prepared MWCNT-PDDA-AuPd showed enhanced electrocatalytic performance toward BPA, which is better than those of homologous monometallic counterparts and MWCNT-PDDA though the content of AuPd is really low. The peak currents of BPA increased with BPA concentration in linear range of 0.18–18 μM and the detection limit of 60 nM. The sensor showed high sensitivity, good stability, repeatability and can be used to detect BPA in milk and water samples with good performance, which demonstrate that MWCNTs-PDDA-AuPd nanocomposite may be an attractive material in applications of environmental and food analysis.